The contribution of neuroscience to the educational field - Aoun , Ali; BENYAHIA, Madani (Journal of Human Sciences, 2020)
Brain research has expanded in recent years due to the emergence of modern technologies and devices that allow researchers to dive deep into the brain. These techniques include imaging by functional magnetic resonance imaging (IRMF) and Positron Emission Tomography, which allows imaging active areas of the human brain during any tasks , Which made brain research based on scientific evidence rather than speculation that prevailed before that. The number of educators interested in studying the relationship between the brain and educational processes increased, as they tried to benefit from the results of these researches in the educational field, through an understanding of the mechanisms of the work of the brain, and from here the intermarriage arose between cognitive neuroscience and education sciences, and then the term Neuro-éducation emerged as a modern discipline In the field of educational and pedagogical applications and adopted by many countries of the developed world in their educational system, and recently some specialists in psychology and education sciences are trying to clarify cognitive neurology to link the link between these disciplines to raise the efficiency of the professor component to better understand the brain No.